Overexpression of a ceramide synthase gene,GhCS1, inhibits fiber cell initiation and elongation by promoting the synthesis of ceramides containing dihydroxy LCB and VLCFA - Li, Guiming; Wang, Qiaoling; Meng, Qian; Wang, Guanhua; Xu, Fan; Chen, Qian; Liu, Fang; Hu, Yulin; Luo, Ming (Frontiers in Plant Science, 2022)
Sphingolipids are important components of biomembrane and bioactive molecules which participate in many processes such as plant growth, development regulation, stimulus sensing, and stress response. Cotton is an important natural fiber crop worldwide. Cotton fiber cell is regarded as an ideal material for studying the growth and development of plant cells. However, the functions of sphingolipids in the cotton fiber development are still unclear. In this study, we identified a cotton ceramide synthase gene, GhCS1, which is predominantly expressed in fiber cell. The GhCS1 is located in the endoplasmic reticulum and has the conserved domains of ceramide synthase. Overexpression of GhCS1 gene inhibited vegetative and reproductive growth in cotton. Importantly, the fiber cell initiation and elongation were severely inhibited when compared with control. The sphingolipid profile group was characterized in the 0 DPA ovule (with fiber cell) of control and transgenic cotton plants. Compared with control, the content of Sph (dihydroxy LCB) decreased significantly, while the content of Phyto-Sph (trihydroxy LCB) did not change in transgenic ovules. Meanwhile, the content of ceramide containing Sph and VLCFA increased significantly while ceramide containing Phyto-Sph and LCFA/VLCFA decreased significantly in transgenic ovules. These results indicated that GhCS1 is a functional ceramide synthase, which preferentially uses Sph and VLCFA as substrates and was different from the Arabidopsis ceramide synthase AtLOH1/AtLOH3, which preferentially used Phyto-Sph and VLCFA as substrates, and also different from AtLOH2, which preferentially used Sph and LCFA as substrates. It is suggested that GhCS1 might be a new ceramide synthase gene in the plant, play some roles in the development of fiber cells and cotton plants.